ALIRAN SESAT DAN GERAKAN BARU KEAGAMAAN (Perspektif UU PNPS No. 1 Tahun 1965 dan Hak Asasi Manusia) - Sumbulah, Umi (De Jure: Jurnal Hukum dan Syari'ah, 2014)
One typology of new religious movements in Indonesia based on the essence of teachings was the group which was considered heretical by the competent authorities, namely the Kingdom of God which led by Lia Aminuddin and al -Qiyadah al-Islamiyah led by Ahmad Moshadeq. Under Act No. PNPS 1 In 1965, the two groups were assessed deviant and criminal breaking so that the perpetrator was sentenced to a maximum of 5 years in prison. Considering the provisions contained in the ICCPR which has been ratified by Indonesia, where the law is contrary to the values of human rights which have been adopted in the constitution and legislation that produced the Reform Era. Legislation which is a product of the Old Order law has been used by New Order for restrictions and co-optation to the development of religious freedom and belief in Indonesia.